Translation, Cross-Cultural Adaptation, and Psychometric Validation of the Russian Coronary Artery Disease Education Questionnaire II (CADE-Q II) in chronic coronary syndrome patients - A. I. Laskova; G. L. M. Ghisi; Yu. M. Lopatin (Российский кардиологический журнал)
Aim. This study sought to translate, cross-culturally adapt, and psychometrically validate the Coronary Artery Disease Education Questionnaire II (CADE-Q II) in Russian.Material and methods. Independent translations and back-translations of the CADE-Q II were conducted by bilingual health professionals and certified translators, respectively. Experts met to consider cultural relevance of the items to Russian patients. The finalized version was then pilot tested in a group of patients to assess understanding and time to complete the tool. Following these steps, 303 patients with a diagnosis of stable coronary artery disease treated in the Outpatient Cardiology Department between April and November 2021 completed the CADE-Q II. The following psychometric properties were evaluated: confirmatory factor analysis, internal consistency (assessed by Cronbach's alpha), test-retest reliability (ICC), and criterion validity (assessed through the association with CADE-Q II and The Self Care of Coronary Heart Disease Inventory and SF-36 scores, among other characteristics from the participants including educational level).Results. After items were translated, revised, culturally adapted and finalized, 30 patients took 30 minutes to complete the CADE-Q II during pilot test and questionnaire was considered understandable by all. Factor analysis (Kaiser-Meyer-Olkin =0.692 and Bartlett's criterion of Sphericity <0.05) revealed four factors, all internally consistent and aligned with the original version of the questionnaire. Cronbach's alpha of subscales ranged from 0.61 to 0.88 and ICC was 0.81. Criterion validity was confirmed by significant differences in total CADE-Q II scores by participants' educational level and correlations between CADE-Q II and The Self Care of Coronary Heart Disease Inventory scores (r=0.251, p<0.05).Conclusion. The Russian CADE-Q II presented sufficient validity and reliability for use to assess disease-related knowledge of chronic coronary syndrome patients in Russia.